2019
DOI: 10.5334/aogh.2418
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease in Latin America

Abstract: Background Latin America covers a vast geographic area (larger than the United States, Canada or Western Europe) with about 600 million inhabitants distributed in at least 19 countries. The population tripled since 1950, with a massive migration from rural areas to cities. Latin America is a mixed pot of ethnicities including the European, African, Mulatto, Mestizo and Amerindian individuals, in various proportions depending on the native population prior to the arrival of Europeans and the extent of European … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 86 publications
1
16
0
3
Order By: Relevance
“…A case series of 1590 patients from China reported a similarly low prevalence of these comorbidities among Chine patients [ 12 ]. The COPD prevalence in Mexico City was 3.4% in a study defining airflow obstruction as FEV1/FEV 6 below the 5th percentile or Lower Limit of Normal [ 23 ], but it has been reported that COPD is highly underdiagnosed in Mexico and in other countries, mainly because of lack of spirometry evaluation [ 24 ]. In a 2009 study, ischemic heart disease and stroke prevalence in Mexico City ranged from 0.4% to 5.4% and from 0.4% to 3.5%, respectively, depending on age [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A case series of 1590 patients from China reported a similarly low prevalence of these comorbidities among Chine patients [ 12 ]. The COPD prevalence in Mexico City was 3.4% in a study defining airflow obstruction as FEV1/FEV 6 below the 5th percentile or Lower Limit of Normal [ 23 ], but it has been reported that COPD is highly underdiagnosed in Mexico and in other countries, mainly because of lack of spirometry evaluation [ 24 ]. In a 2009 study, ischemic heart disease and stroke prevalence in Mexico City ranged from 0.4% to 5.4% and from 0.4% to 3.5%, respectively, depending on age [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed data from smoking-induced COPD because there is a lack of information on early diagnosis in nonsmoking patients with COPD. However, in regions such as Latin America, more than one-third of patients with COPD were never-smokers, which determines that a significant proportion of patients adopt strategies based on similarities with cigarette smoke-induced COPD (symptoms, obstructions, exacerbations), rather than on scientific evidence [71].…”
Section: Limitationsmentioning
confidence: 99%
“…Análisis más recientes de esta misma información estiman una prevalencia real cercana al 4%, la segunda más baja conocida para una ciudad, al igual que la mortalidad, que podría sufrir las mismas diferencias significativas territoriales en nuestro país. 4,5 El subdiagnóstico y el error diagnóstico de la EPOC son uno de los escenarios más desafiantes para México y el mundo. En el estudio PLATINO esto se evidenció cuando mostró que el 86% de las personas con EPOC no habían sido diagnosticadas (subdiagnóstico).…”
Section: Wwwmedigraphicorgmx 2: La Carga De Epoc En Méxicounclassified